Preparation of Antioxidant Peptides from Chicken Bone Proteins and the Influence of Their Compositional Characteristics on Antioxidant Activity - Yitong Jin; Peng Zhou; Chengzhi Zhu; Yanan Liu; Zhijun Zhao (Foods)
Antioxidants play an important role in maintaining health and enhancing food stability by neutralizing free radicals. This study aimed to extract antioxidant peptides from white-feathered chicken bones through enzymatic hydrolysis, optimize the enzymatic hydrolysis conditions, and further investigate the relevance between the amino acid composition, molecular weight, and antioxidant activity of the resulting chicken bone hydrolysate. Alcalase was the most effective enzyme for hydrolyzing cooked chicken bones compared with papain, pepsin, and trypsin, yielding hydrolysates with the highest DH and ABTS radical scavenging activity. The enzymatic conditions were optimized using single-factor experiments and response surface methodology (RSM). The optimal conditions were a substrate concentration of 10%, an enzyme-substrate ratio of 502.75 U/g, a hydrolysis temperature of 48.48 °C, and a hydrolysis time of 1.13 h. Under these conditions, the ABTS radical scavenging activity reached 83.43%. Amino acid composition analysis revealed that peptides from chicken bones were rich in glycine, glutamic acid, alanine, proline, and aspartic acid, which were associated with antioxidant functions. Among these peptides, those with a molecular weight below 3 kDa exhibited the highest antioxidant effects through membrane filtration. In summary, chicken bone hydrolysate exhibits potent antioxidant activity, nominating them for potential application as natural antioxidants investible in novel functional foods and pharmaceuticals.